Acceptance Sampling Plans from Life Tests Based on Percentiles of Half Normal Distribution. (3rd December 2013) - Rao, B. Srinivasa; Kumar, Ch. Srinivasa; Rosaiah, K.
Abstract : The design of acceptance sampling plans is developed under truncated life testing based on the percentiles of half normal distribution. The minimum sample size necessary to ensure the specified life percentile is obtained under a given consumer's risk. The operating characteristic values of the sampling plans as well as the producer's risk are presented. The results are illustrated by examples.